Description of the Nutritional Status of Children Under Five Years of Age in the Province of Yogyakarta in 2023 - Nurcholid Umam Kurniawan; Dewi Yuniasih; Andrianto Selohandono; Febrianti Putri Nurulita (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2024)
Background: The nutritional status of children under five is a measure that describes the health condition of children under five based on the balance between nutrient intake and body needs for optimal growth, development, and body function. The nutritional status of children under five in the Special Region of Yogyakarta (DIY) in 2023 includes various important indicators such as stunting, wasting, and underweight. Objective: To provide a comprehensive picture of the nutritional status of children under five in Yogyakarta in 2023. Methods: The research design used was descriptive with a quantitative approach. The population in this study was all toddlers living in the Special Region of Yogyakarta in 2023. The sampling technique is purposive sampling, so that the data taken is data on toddlers aged 0-59 months who live in DIY and are contained in the SKI 2023. The data collection method used secondary data, namely the 2023 Indonesian Health Survey (IHS) data. Results: Stunting was highest in Gunungkidul (22.2%) and lowest in Sleman (12.4%). Underweight also had a significant prevalence, especially in Bantul (14.7%) and Gunungkidul (14.5%). Wasting had the highest prevalence in Bantul (7.9%). Conclusion: The most prevalent under-five nutritional status problem is stunting.